The President of the Energy Regulatory Authority in relation to energy policy in Poland - Rejmus, Marcin (Przegląd Prawniczy Uniwersytetu im. Adam Mickiewicza, 2014)
The subject matter of the essay is the tasks of the President of the Energy Regulatory Authority in relation to energy policy in Poland. The essay is divided into two parts. The first part presents basic information about the national regulatory authority, regulation and kinds of energy policy. The second focuses on the tasks of the President of the Energy Regulatory Authority in various areas, such as: energy effectiveness, energy security, renewable forms of energy and competition in the energy market. The article examines the tasks carried out by the President in the past and those which must come into force in the future to modernize the Polish energy market. Finally, the author thrashes out the legal relations between the functions of the President of the Energy Regulatory Authority and the aims mentioned in Polish energy policy. The author pays special attention to the problems of liberalisation in the energy market in Poland.